A RECORD OF AQUATIC HEMIPTERA OF GHARANA WETLAND, JAMMU - J. S. TARA; RAMNIK KOUR; SUNIL SHARMA (The Bioscan, 2011)
The present study was aimed to record the commonly occuring aquatic Hemiptera of Gharana wetland. Specimens were collected from September, 2008 to August, 2009. A total of 14 species of order Hemiptera belonging to nine families viz. Corixidae, Belostomatidae, Nepidae, Notonectidae, Hydrometridae, Pleidae, Mesovelide, Vellidae and Gerridae have been recorded in the present investigation. Families Nepidae and Corixidae represent the highest number of species (three species). Sphaerodema annulatum (Belostomatidae) was reported for the first time from Jammu.